Integrating Transcriptomic and Metabolomic Analyses to Explore the Effect of Color Under Fruit Calyx on That of Fruit Apex in Eggplant (Solanum melongena L.) - Zhang, Jingjing; Li, Bing; Gao, Xiurui; Pan, Xiuqing; Wu, Yanrong (Frontiers in Genetics, 2022)
Fruit color is an important commercial characteristic of eggplant (Solanum melongena L.), which affects both the profits of growers and consumer choice. Two eggplant inbred lines were discovered: “Z,” which is a light purple color under the fruit calyx, with purple on the fruit apex; and “L,” fruits of which are green under the calyx and at the apex. To determine the molecular mechanisms underlying the effect of fruit peel color under the calyx on that at the fruit apex, we conducted a combined transcriptomic and metabolomic analyses of the Z and L inbred eggplant lines. Transcriptome analysis of peel samples from three fruit regions (under the calyx, the apex, and the middle surface) of each line was conducted by RNA sequencing, and generated a total of 791,512,404 clean reads from 18 samples (three biological replicates). Differentially expressed genes (DEGs; n = 424) were identified in comparisons of peel samples from the three sites of L line fruits. Gene ontology analysis showed that “catalytic activity” was extremely significantly enriched. Further, DEGs (n = 8) were enriched in the Kyoto Encyclopedia of Genes and Genomes pathway “flavonoid biosynthesis.” Levels of CHI, LDOX, F3′5′H, and dihydroflavonol reductase were higher in the Z line than the L line. In addition, metabolome analysis showed that, 10 differentially accumulated metabolites were detected between peel samples from the apex of L and Z line fruit. The most significant DAM was delphinidin-3-O-rutinoside (Z line content, 34.89 μg/g vs. L line content 0.01 μg/g). Combined transcriptomic and metabolomic analyses indicated that DFR and F3′5′H were closely related to content of the metabolites, cyanidin and delphinidin, and that some downstream metabolites differed significantly between the L and Z lines. Content levels of delphinidin-3-O-rutinoside, delphinidin-3-O-glucoside, cyanidin-3-O-glucoside, and cyanidin-3-O-rutinoside were markedly down-regulated in the L line. Altogether, increased CHI levels could up-regulate the downstream genes, LDOX, F3′5′H, and DFR, which further lead to increasing the content of delphindin. Thus, the uniform purple color was presented at the apex of fruits in Z plants. These findings not only identify key candidate genes, but will also improve understanding of the genetics and the efficiency of breeding for eggplant fruit color.